Phranakhon Si Ayutthaya Member of the House of Representatives - นาคธน, วิชชุกร (Journal of Educational Review Faculty of Education in MCU, 2018)
This research aims to 1) to study the characteristics of provincial politicians; (Member of the House of Representatives) Phra Nakhon Si Ayutthaya from the beginning in the first election in 1933 to the present. 2) Another purpose this research made was to learn about political networks and relationships Ayuthaya politicians established in order to organize their staff, run their electoral campaign, as well as deal with their political party. The methodology used in this research relies primarily on qualitative methods consisting of documentary and explanatory research, interviews, and group discussions. The major result is that The characteristics of Ayuthaya politicians can be divided into three periods of time. The first period is between 2476 and 2512 B.E. when the major factors that had the most impact on the chance to win in the election were the politicians’ personal characteristics such as educational backgrounds and occupations (which in this case mostly were retired government officers, lawyers, or businessmen). The main reason for this succession is because those groups of people had a great connection with local or community leaders whom people in the province paid their respect to. Another interesting point this research found is that personal characteristics that related to the relations between politicians and their canvassing networks was not depended largely on individual benefits at this period. The second period, between 2512 and 2518 B.E., is a transitional period in which several political changes had occurred such as student uprising in October 2516. The third period is since 2518 B.E. until current in which money, personal interest, political power, and ability in dealing with campaign management have been the very important factors that determinate whether the politicians win in the election. The occupation background of the politicians in this period has no longer been the retired government officers or lawyers but most of all businessmen. 3. The success politicians at this time established a strong relation with local business, politicians at local level as well as high positioned government officers. Moreover, politicians in this period have changed their campaign strategies from conducting an intensive field visit to campaign management in particular by establishing a strength canvasser-network.